Annual Incidence and Risk Factors of Febrile Convulsions in Alwahda Hospital, Derna-Libya a Prospective Study During 2007 - Bojeldein, Salem; El Shourbagy, Omar Al Sayed (جامعة عين شمس - كلية الدراسات العليا للطفولة, 2008)
يهدف البحث إلى دراسة وتقدير معدلات وعوامل الإختطار للتشنجات الناتجة عن الحرارة للحالات التي أدخلت بمستشفى الوحدة بدرنه- ليبيا خلال 2007، وقد أجريت دراسة للحالات والتاريخ المرضي والعائلي، وتحديد نوع التشنجات ومدتها والأعراض المصاحبة، كما تم إجراء تحاليل في الدم لنسب الصوديوم والبوتاسيوم والسكر والهيموجلوبين والتحليل الكيميائي لسائل النخاع الشوكي. وأظهرت النتائج أن معدل الإصابة السنوي للتشنجات الناتجة عن الحرارة هو 75/1000 طفل، وكانت النسبة الأكبر في الفترة العمرية من 3 شهور إلى سنتين 70.2 في المائة من الحالات، وكانت التهابات الجهاز التنفسي العلوي من أكثر الأسباب المؤدية إلى التشنجات الناتجة عن الحرارة حيث مثلت 75 في المائة من الحالات ثم النزلات المعوية حيث مثلت 10.2 في المائة ثم التهابات المسالك البولية حيث مثلت 5.5 في المائة من الحالات. وكان التاريخ العائلي إيجابي في 2.8 في المائة من الحالات، ولا توجد فروق، ودلالة إحصائية في تحاليل الدم وسائل النخاع الشوكي. ويخلص البحث أن التشنجات الناتجة عن الحرارة من أكثر المشاكل الشائعة في الأطفال وتتفق نتائج البحث مع توصيات الأكاديمية الأمريكية لطب الأطفال على أنه ليس من التحاليل الروتينية للتشنجات الناتجة عن الحرارة إجراء تحاليل لأملاح الدم. Aim: To analyze febrile convulsions (FC) regarding annual incidence and risk factors during one-year period in Alwahda Hospital, Derna- Libya. Material and methods: A prospective study of children diagnosed to have febrile concisions from January 2007 to December 2007, admitted to Alwahda Hospital, Derna-Libya were included in the study. Detailed family history was taken, type of convulsions, its duration, associated symptoms and detailed family history was recorded. Investigations (sodium, calcium, potasstum, glucose, hemoglobin and CSF analysis) were done. Children with history of congenital anomalies, CNS infection and metabolic condition were excluded. Results: Of 1434 admissions during this period, 107 children were diagnosed to have febrile convulsions with an annual incidence of 75/1000 children. Of this 66 (61.7%) were males and 41(38.3%) females (male- female ratio 1.6:1). Age ranged from 3 months to 6 years. FC was most common (70.2%) in children between 3 months and 2 years of age. Five cases (4.8%) had complex FC. Convulsions were associated with URI in 80 (75%), gastroenteritis in 11 (10.2%), UT1 in six (5.5%) and no specific cause for fever was found in 10 (9.3%) of cases. Family history of FC was present in 2.8% of children. Temperature was significantly higher in complex FC than simple FC cases (P=0.04). There was a significant negative correlation between blood glucose and the duration of the convulsion (r=0.25, P=0.014). No statistical significant differences were found in the levels of sodium, calcium, potassium, glucose, hemoglobin and CSF analysis between simple and complex FC cases. Convulsions were of generalized tonic clonic type. Conclusion: Febrile convulsion is considered one of the most common problem in pediatric practice. Our findings reaffirm the recommendation of the American Academy of Pediatrics Practice Parameter not to routinely obtain electrolytes.
Keywords: أمراض الأطفال; ليبيا; التشنجات عند الأطفال